UJI EFEKTIVITAS ANTIBAKTERI SEDIAAN KRIM TIPE M/A DARI MINYAK ATSIRI KULIT BUAH JERUK PONTIANAK (Citrus nobilis Lour. var. microcarpa) TERHADAP ISOLAT Propionibacterium acnes SECARA IN VITRO - ., Neny Lucyani (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Acne is a skin disorder which is caused by the Propionibacterium acnes bacteria. One of thesubstances that can be benefitted as an antibacterial product is Pontianak citrus (Citrus nobilisLour. Var. Microcarpa) peel essential oil. Essential oil is obtained through the process ofsteam distillation. This study aims to determine the effect of formulated antibacterial creamof essential oil of Pontianak citrus’ peel to P. acnes isolates by disc diffusion method (KirbyBauertest).EssentialoilsformulatedindosageformscreamwithessentialoilconcentrationratioF1 (0.025%), F2 (0.05%) and F3 (0,1%). Evaluation of organoleptic examinations ofsuch preparations include odor, color, shape and homogeneity, dispersive power testing,adhesion, pH and antibacterial. Data analysis is done by using the R-Commander programversion 2.14.1. The results showed that the inhibitory zone in F1, F2 and F3 is 18mm, 20mmand 21,67mm. The evaluation results indicate a homogeneous preparation, pH is inaccordance to the peel’s pH and there is a decrease of adhesion and increase of dispersivepower. The results of antibacterial cream evaluation showed that formula 1 gives the besteffectiveness with inhibition zone of 18 mm to the P. acnes isolates. Keyword: Acne, Pontianak citrus peel essential oil, P. acnes